1990
DOI: 10.1111/j.1365-2265.1990.tb03915.x
|View full text |Cite
|
Sign up to set email alerts
|

Tsh Secretion In Cushing's Syndrome: Relation To Glucocorticoid Excess, Diabetes, Goitre, And The ‘Sick Euthyroid Syndrome’

Abstract: Thyrotrophin (TSH) secretion was studied in 63 patients with Cushing's syndrome (53 patients with pituitary dependent Cushing's disease, eight with adrenocortical tumours, and two with the ectopic ACTH syndrome). Prior to treatment, TSH response to 200 micrograms of TRH intravenously was significantly decreased compared to controls; TSH response was 'flat' (increment less than 2 mU/l) in 34 patients (54%). Patients with a flat response to TRH had significantly higher morning and midnight cortisol levels than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
7

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 26 publications
5
44
0
7
Order By: Relevance
“…Another TSH profile study in pituitary-dependent hypercortisolism, comprising three patients, reported decreased pulsatile TSH secretion with different analytical techniques (19). Our findings are also in keeping with previous reports documenting decreased efficacy of TRH in inducing TSH release in patients with hypercortisolism and in healthy subjects after glucocorticoid administration, and suggesting a relationship between the degree of glucocorticoid excess and impairment in the TSH response (10)(11)(12). Indeed, a single dose of glucocorticoids (1-2 mg dexamethasone) causes an acute decrease in pulsatile TSH production in healthy men (9).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Another TSH profile study in pituitary-dependent hypercortisolism, comprising three patients, reported decreased pulsatile TSH secretion with different analytical techniques (19). Our findings are also in keeping with previous reports documenting decreased efficacy of TRH in inducing TSH release in patients with hypercortisolism and in healthy subjects after glucocorticoid administration, and suggesting a relationship between the degree of glucocorticoid excess and impairment in the TSH response (10)(11)(12). Indeed, a single dose of glucocorticoids (1-2 mg dexamethasone) causes an acute decrease in pulsatile TSH production in healthy men (9).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, levels were decreased in patients with hypercortisolism, although in all cases serum fT 4 concentration levels remained within normal limits as reported in other studies (11,12,19). A possible explanation for the relatively normal T 4 concentrations during hypercortisolism is that the biological activity of TSH was increased by altered posttranslational processing of the oligosaccharide chains of the TSH molecule (44).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been described that most of the patients with NTIS have normal TSH responses in the TRH stimulation test 4 . A normal response in the presence of a low basal TSH can suggest an hypothalamic abnormality 10,27,28 . It has been shown that the reduction of the glycosylation process of the TSH molecule makes it immunologically active and biologically inactive and this process is dependent on the TRH levels 10,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the HPA axis is associated with decreased production of thyroidstimulating hormone and inhibition of conversion of the relatively inactive thyroxine to the more biologically active triiodothyronine in peripheral tissues (the "euthyroid sick" syndrome). [89][90] Although the exact mechanism for these phenomena is not known, both phenomena may be caused by the increased levels of glucocorticoids and may serve to conserve energy during stress. Inhibition of thyroid-stimulating hormone secretion by CRH-stimulated increases in somatostatin might also participate in the central component of thyroid axis suppression during stress.…”
Section: Thyroid Axismentioning
confidence: 99%